2004
DOI: 10.1007/s10147-004-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between overlapping structure-based and non-overlapping structure-based optimization for simultaneous integrated boost IMRT for malignant gliomas

Abstract: The two optimization methods provided comparable dose distributions within the target volumes and normal brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…We have already reported the details of the target volume delineation in this clinical trial, in which the contouring of PTV-G and PTV-a was graphically demonstrated. 6,12 Treatment planning A commercial treatment-planning system (Cadplan Helios ver.6.01; Varian Associates, Palo Alto, CA, USA) was used. The IMRT beam arrangements consisted of fi ve coplanar beams.…”
Section: Target Volume Delineationmentioning
confidence: 99%
“…We have already reported the details of the target volume delineation in this clinical trial, in which the contouring of PTV-G and PTV-a was graphically demonstrated. 6,12 Treatment planning A commercial treatment-planning system (Cadplan Helios ver.6.01; Varian Associates, Palo Alto, CA, USA) was used. The IMRT beam arrangements consisted of fi ve coplanar beams.…”
Section: Target Volume Delineationmentioning
confidence: 99%